2021
DOI: 10.3389/fcell.2021.718721
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Stem Cell-Derived ANXA6-Containing Exosomes Sustain Paclitaxel Resistance and Cancer Aggressiveness in Breast Cancer

Abstract: Continuous chemotherapy pressure-elicited annexin-A6 (ANXA6)-containing exosome (ANXA6-exo) secretion contributes to paclitaxel (PTX) resistance in breast cancer (BC), but the molecular mechanisms are not fully elucidated. The present study managed to investigate this issue and found that ANXA6-exo promoted PTX resistance and cancer progression in BC cells in a Yes-associated protein 1 (YAP1)-dependent manner. Specifically, the parental PTX-sensitive BC (PS-BC) cells were exposed to continuous low-dose PTX to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Elevated ANXA6 has been proved to increase drug resistance by regulating autophagy in various tumors [ 46 , 93 , 94 ]. ANXA6-EVs induced by continuous chemotherapeutic pressure promotes drug resistance, cell migration, stemness, and autophagy in paclitaxel-sensitive breast cancer cells [ 95 ]. ANXA6-EVs up-regulate yes-associated protein (YAP) to promote dysregulation of the Hippo pathway, contributing to the development of tumor resistance to some extent.…”
Section: Anxa6 and Cancer Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Elevated ANXA6 has been proved to increase drug resistance by regulating autophagy in various tumors [ 46 , 93 , 94 ]. ANXA6-EVs induced by continuous chemotherapeutic pressure promotes drug resistance, cell migration, stemness, and autophagy in paclitaxel-sensitive breast cancer cells [ 95 ]. ANXA6-EVs up-regulate yes-associated protein (YAP) to promote dysregulation of the Hippo pathway, contributing to the development of tumor resistance to some extent.…”
Section: Anxa6 and Cancer Drug Resistancementioning
confidence: 99%
“…ANXA6-EVs up-regulate yes-associated protein (YAP) to promote dysregulation of the Hippo pathway, contributing to the development of tumor resistance to some extent. In addition, silencing YAP could counteract the effects of ANXA6-EVs on paclitaxel resistance and cancer aggressiveness in bladder cancer cells [ 95 ]. In nasopharyngeal carcinoma, ANXA6 promotes protective autophagy by inhibiting the PI3K/AKT signaling pathway, thereby promoting radioresistance [ 94 ].…”
Section: Anxa6 and Cancer Drug Resistancementioning
confidence: 99%
“…Doheny et al ( 68 ) reported that knockdown of SMO inhibited BCSC growth, suggesting that Hedgehog pathway inhibitors may be useful in BCSC-targeted therapy. In addition, further signal transduction pathways, including the Hippo ( 69 ), TGF-β ( 70 ), JAK2/STAT3 ( 71 ) and PI3K/AKT/mTOR ( 72 ) pathways, are closely associated with BCSCs through their effects on BC occurrence and progression.…”
Section: Bcscs and Related Signaling Pathwaysmentioning
confidence: 99%
“…In breast cancer, ANXA6 present in exosomes from stem cells promoted paclitaxel resistance via YAP1 upregulation. ANXA6 also promoted cell migration, autophagy, cell growth and stem properties ( Guo et al, 2021 ). In addition, ANXA6 has been involved in resistance to EGFR-TKIs such as lapatinib in TNBC, where ANXA6 upregulation is part of an adaptive mechanism to acquire resistance ( Widatalla et al, 2019 ).…”
Section: Annexin A6mentioning
confidence: 99%